Global/local knowledge organization: Contexts and questions - Adler, Melissa A.; Tennis, Joseph T.; Martínez-Ávila, Daniel [UNESP]; Guimarães, José Augusto C. [UNESP]; Mai, Jens-Erik; Olesen-Bagneux, Ole; Skouvig, Laura (Wiley, 2016)
This panel features junior and senior scholars from the United States, Denmark, and Brazil, who will come together to discuss some of the central tensions between local and global knowledge organization systems. They will be in conversation around three key questions: 1) What are the contexts in which local and global knowledge organization systems matter? 2) What can we learn about the stakes of global/local knowledge organization from those contexts? 3) How can we conceptualize the relationship between the universal and the particular? The panelists will provide brief overviews of their perspectives, and the majority of the time will be reserved for an interactive discussion of the epistemological, practical, and ethical dimensions of global and local knowledge organization. The contexts addressed will include libraries, archives, and digital, social, and popular media. Within those settings, the panelists are concerned with such issues as access, hegemony, intended and unintended consequences, and meaning construction in particular domains, spaces, and communities.
Keywords: classification; Global knowledge organization systems; local knowledge organization systems; universal knowledge organization systems